Implementation of Information System Based on Website as Introduction to Sumbawa's Typical Sakeco Oral Literature - Herfandi Herfandi; Idham Amdin (ULTIMA InfoSys, 2022)
Indonesia is an archipelago that is very rich in traditional culture. Traditional culture plays an essential role in attracting tourists. Sakeco is a traditional culture of the Sumbawa tribe. If people do not know and know the existing culture, it will not be easy to preserve today's culture. Poto Village dance studio still uses a manual process that causes inefficient processes. Information systems have been widely implemented to preserve culture. Hence this research carried out the implementation of information systems to introduce sakeco oral literature. This research produced a website-based sakeco oral-literary recognition system with admin features: Posts to add new posts, problem data by creating, recording, updating, deleting, and searching for quiz needs, users to view admin data, and settings to organize posts and website views. While users: do quizzes and see answers as a learning medium, see the history of sakeco, sakeco verse, sakeco anorawi, and sakeco anosiup, and latest posts to see the latest posts and popular posts to see the most opened posts. Development methods using waterfall, designing methods using Unified Modeling Language, black-box testing get results as expected from various functionality tests. This information system is expected to help the poto village dance studio, indigenous and outer people of Sumbawa. They want to know and know Sumbawa's typical oral literature (sakeco) and become one of the ways to maintain and preserve the tradition of sakeco verse in the Sumbawa area.